COMPUTER SIMULATION OF DEAD-END MINE WORKING VENTILATION - Biliaieva, V. V.; Kirichenko, P. S.; Gunko, E. Y.; Bondarenko, I. O.; Mashykhina, P. B.; Yakubovska, Z. M. (Science and Transport Progress, 2019)
Purpose. The important problem in the field of ecological safety and industrial safety is providing of normal microclimate in dead-end mine working. In these regions of the mine methane gas can be accumulated and as a result explosion may take place. So, to avoid these accidents it is important to ventilate appropriately dead-end mine working. The purpose of the work is development of quick computing mathematical model to obtain information about dead-end mine working ventilation process. Methodology. The process of dead-end mine working ventilation computing is separated in two stages. At the first stage the velocity flow field is computed in the dead-end mine working. We consider the situation when the suction tube is situated in this region. To solve this problem the fluid dynamics model of inviscid gas flow was used. At the second stage of the computational modeling the convective- diffusive equation of admixture transfer was used. The equation takes into account non-uniform flow field in the dead end mine workings. Findings. The developed numerical model was coded using FORTRAN language. The developed computer code allows to perform numerical experiment to assess the efficiency of suction tube implementation to decrease methane gas concentration in dead-end mine working. Originality. The developed numerical model takes into account physical factors, which are not considered nowadays in the empirical models, which are used for solving the problems of dead-end mine working ventilation. It allows taking into account the geometrical form of the dead-end mine working. Practical value. The developed computer program allows to perform calculations to assess the efficiency of suction system used for the ventilation of the dead-end mine working.